Impacts of Light Quality on the Growth and Development of Pyropia kinositae Conchocelis - Yuqi DUAN; Zhourui LIANG; Hui XU; Xiaoping LU; Yanmin YUAN; Wenjun WANG (Progress in Fishery Sciences)
Pyropia kinositae is an ideal candidate for offshore cultivation of laver, but there is room for improvement in seedling breeding techniques. Light serves as a crucial energy source and regulatory signal for algal growth and development. However, research on the role of light quality in regulating the growth and development of laver is still scarce. This study extensively investigated the effects of different light qualities (red, green, blue, and white light) on vegetative conchocelis, the transition from vegetative conchocelis to conchosporangial phase, the formation of bipartite cells in conchosporangia, and conchospore release of P. kinositae. We also examined the chlorophyll fluorescence characteristics of conchocelis under different light qualities. The results showed that relative growth rate of conchocelis under blue light was significantly higher than that under other light qualities, indicating that blue light is more suitable for the expansion of vegetative conchocelis. Under blue light, the actual quantum yield [Y(Ⅱ)], maximum electron transport rate (rETRmax), and the minimum saturating irradiance (Ek) of conchocelis as well as the maximal quantum yield of Photosystem Ⅱ (Fv/Fm) of conchospores were significantly higher than those under other light qualities. This suggests that blue light significantly enhances the photosynthetic efficiency of conchocelis and improves its electron transfer activity and phototolerance under high light conditions. In contrast, Y(Ⅱ) and rETRmax of conchocelis under red light were significantly lower than those under other light qualities. Under blue light, the conversion rate of conchocelis to conchospores (48.7%) and the rate of bipartite cells in conchosporangia formation (26.7%) were significantly higher than those under other light qualities, indicating that blue light significantly promotes the synchronous maturation of conchocelis, followed by white and green light, whereas red light did not show a significant effect. When inducing the conchospore release from conchocelis with consistent maturity, the early release of conchospores did not significantly vary under white, red, and green light, but a significant increase was observed under blue light, indicating that blue light promotes the release of bipartite cells. The germination rate of conchospores under red and green light was low (< 10%), whereas it was significantly higher (> 80%) under blue light compared with the other light qualities. These results provide preliminary insights into light quality conditions and the photosynthetic physiological basis for promoting the growth and development of P. kinositae conchocelis and muturation and release of conchospores, offering theoretical support for the regulation of light in seedling production.